Uzbekistan : Overview of Climate Change Activities - World Bank (Washington, DC, 2014)
This overview of climate change activities in Uzbekistan is part of a series of country notes for five Central Asian countries that summarize climate portfolio in a number of sectors, namely agriculture, forestry and natural resources, water, health, energy, and transport. The note further provides a brief overview of Uzbekistan's climate context in terms of observed impacts and historical trends as well as climate projections specific to sectors that are considered to be essential to the country's economic development. Finally, the note assesses national policy and institutional context related to climate change as well as suggests potential ways forward that could help Uzbekistan mainstream climate considerations into development activities and planning and create public demand for climate actions.